PENGARUH KARAKTERISTIK CORPORATE GOVERNANCE TERHADAP EFFECTIVE TAX RATE (ETR) - PUJI NIA LESTARI; djoko wahyudi (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
Taxes are very important because taxes make a large contribution to state revenue. This study aims to analyze the effect of independent commissioners, audit committees, and institutional investors. The sample of this research is state-owned companies listed on the Indonesia Stock Exchange from 2016 to 2019 so that in this study 66 data were used. Descriptive statistical test and multiple regression test with SPSS 26 were used to analyze the data. This study shows that the independent commissioner variable has no effect on the effective tax rate, the audit committee has a significant negative effect on the effective tax rate, institutional investors have no effect on the effective tax rate. On the other hand, size, leverage, profitability have no effect on the effective tax rate, and the ratio of capital intensity has a positive effect on the effective tax rate.